Flavanones as Modulators of Gut Microbiota and Cognitive Function - Natalia Cichon; Rafał Szelenberger; Maksymilian Stela; Marcin Podogrocki; Leslaw Gorniak; Michal Bijak (Molecules)
Flavanones, a key subclass of flavonoids, exhibit a wide range of biological activities, including antioxidant, anti-inflammatory, and neuroprotective properties. Predominantly found in citrus fruits, they occur in both aglycone and glycosylated forms, undergoing extensive metabolic transformation upon ingestion. Recent evidence suggests that flavanones, such as naringenin and hesperidin, influence gut microbiota composition, fostering a balance between beneficial and pathogenic bacterial populations. The gut microbiota plays a pivotal role in regulating the gut–brain axis, impacting cognitive function through the production of short-chain fatty acids (SCFAs), neurotransmitters, and anti-inflammatory cytokines. The modulation of the gut microbiome by flavanones has been associated with improvements in cognitive performance and a reduced risk of neurodegenerative disorders. This review provides a comprehensive analysis of the characteristics of major flavanones, their metabolic pathways, and their impact on gut microbiota and cognitive function. It covers the fundamental mechanisms through which flavanones exert their effects, as well as their potential therapeutic applications for brain health and neuroprotection. Despite promising findings, further research is needed to determine optimal dosages, strategies to enhance bioavailability, and long-term safety profiles.